Anterior Segment Anatomic Parameters Based on the Scleral Spur and Cornea for Risk Profiling of Primary Angle Closure Glaucoma - Yue Fu; Bin Jiang; Yang Liu; Lufan Li; Yuting Li; Zhaohui Chang; Wen Zeng; Min Ke (Ophthalmic Research)
Introduction: The aim of the study was to investigate the anterior segment anatomical parameters associated with the scleral spur and cornea for risk profiling of primary angle closure glaucoma (PACG). Methods: A retrospective study was conducted, collecting parametric measurements obtained using CASIA 2 and IOLMaster 700. Univariate and multivariate logistic regression models were utilized to compare ocular parameters between the narrow angle (NA) group and PACG group, as well as identify risk factors for PACG. The predictive performance of each parameter was evaluated using the area under the receiver operating characteristic (AUROC) curve. Results: A total of 84 patients with PACG (48 with PACG and 36 with chronic PACG) and 84 patients with NA were included in this study. In the multivariable model, it was demonstrated that individuals with a smaller trabecular scleral-spur angle (TSA: OR = 0.810, per 1° increase, p < 0.001, AUROC = 0.738) and larger relative lens vault (rLV: OR = 1.112, per 1 percent increase, p < 0.001, AUROC = 0.720) had an increased risk of developing PACG. Furthermore, combining TSA with rLV yielded an improved AUROC value of 0.807 (p < 0.001). Conclusion: AS-OCT is a valuable tool for early assessment of progression risk in NA patients at risk for developing PACG. Our findings suggest that both TSA and rLV are significant risk factors for PACG. Moreover, the novel parameter TSA demonstrates promising potential as a predictive tool for early PACG screening.